2019
DOI: 10.1210/jc.2018-02094
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-Hydroxyvitamin D Concentrations at Birth in Children Screened for HLA-DQB1 Conferred Risk for Type 1 Diabetes

Abstract: Context Vitamin D has several effects on the immune system that might be of relevance for the pathogenesis of type 1 diabetes (T1D). Objective To evaluate whether umbilical cord serum concentrations of 25-hydroxy-vitamin D (25[OH]D) differ in children developing either islet autoimmunity (IA) or overt T1D during childhood and adolescence. Design Umbilical cord serum samples from 764 children born from 1994 to 2004 with HLA-DQB1 conferred risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Our results do not support a strong role for vitamin D in the disease process leading to type 1 diabetes. This is consistent with results from the DIPP and DAISY birth cohort studies [2][3][4]. Recent findings suggest that vitamin D deficiency may be a risk factor for those carrying certain genotypes of the VDR gene [5,13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results do not support a strong role for vitamin D in the disease process leading to type 1 diabetes. This is consistent with results from the DIPP and DAISY birth cohort studies [2][3][4]. Recent findings suggest that vitamin D deficiency may be a risk factor for those carrying certain genotypes of the VDR gene [5,13].…”
Section: Discussionsupporting
confidence: 89%
“…Large birth cohort studies that have invited participants based on an increased genetic risk for type 1 diabetes have analysed the association between serum 25OHD concentration and type 1 diabetes. The Finnish Diabetes Prediction and Prevention (DIPP) study [2,3] and the Diabetes Auto Immunity Study in the Young (DAISY) [4] did not find any association between serum 25OHD concentration and risk of islet autoimmunity or type 1 diabetes at birth or during childhood, whereas the Environmental Determinants of Diabetes in the Young (TEDDY) study reported an association between low serum 25OHD concentration during childhood and increased risk of islet autoimmunity [5]. A Norwegian study found an association between maternal low serum 25OHD concentrations and increased risk for type 1 diabetes in the offspring [6], whereas in Finland such an association was not seen in a similar study setting [7].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, 25(OH)D, the standard metric for vitamin D, did not predict PE; of note, however, insufficient or deficient levels were almost universal in our diabetic cohort. Reported associations of vitamin D deficiency in diabetic pregnancy include preterm birth, increased T1DM rates in offspring of women with T1DM, and poor glycemic control [12,17,20,21,29]. Some studies in non-diabetic pregnant women have suggested that low total 25(OH)D is associated with contemporaneous [10] or subsequent PE [9,12], perhaps limited to early-onset disease [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, the plasma concentration of 25-hydroxyvitamin D (25(OH)D), the prohormone and precursor of 1,25(OH) 2 D, is considered the principal metric for assessing vitamin D status: deficiency and insufficiency are defined as <20 and <32 ng/mL (<50 and <80 nmol/L), respectively [7]. Vitamin D deficiency is associated with poor pregnancy outcomes for both mother and child [2,[8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Both 25(OH)D and 1,25(OH) 2 D can be measured in plasma as total, bioavailable, and free forms; both metabolites are highly lipophilic and, in plasma, are almost entirely protein-bound.…”
Section: Introductionmentioning
confidence: 99%
“…This could explain the reported controversial results. A recent study shows that the integration of vitamin D with ω-3 co-supplementation and arachidonic acid reduction in the Mediterranean diet have benefits for T1D children at onset (40 (41). Although these results add relevant information on the risk of T1D, other components still need to be evaluated.…”
Section: Dietmentioning
confidence: 99%